An Analysis of Picture and Picture Method in Japanese Vocabulary Mastering at the Japanese Internship Institution Terayoka Bali - Sutarmaya, I Made Abdi; Suparwa, I Nyoman; Aryani, Made Ratna Dian (LPPM Universitas Dhyana Pura, 2022)
This study aims to analyze (1) the students' capability to master Japanese vocabulary at the basic level of class B-2 before and after applying the picture and picture method; (2) the effectiveness of the picture and picture method that influences the advancement of students' Japanese vocabulary mastery. This research employed a descriptive qualitative method conducted on 20 students at LPK Terayoka Bali. In line with that, the data collection techniques were tests, questionnaires, and observations. The test was delivered twice, namely a pre-action evaluation and a conclusive test after the treatment. Data collection was maintained through questionnaires distributed after administering the test and observing the class process during treatment delivery. The results revealed that the picture and picture method could enhance students' Japanese vocabulary mastery of nouns, adjectives, and verbs. Moreover, the students' average scores attainment of the pre-action evaluation compared to the final test after treatment can confirm the students' ability enhancement. The total average score of students based on the results of the pre-action evaluation is 35.8, advancing the conclusive evaluation outcome after treatment to an average score of 81. The low outputs of student pre-action evaluations were caused by learning methods applications that were not under the students' learning needs in mastering the vocabulary of nouns, adjectives, and verbs. In addition, the picture and picture method application in the learning process influences the increasing students' ability to master Japanese vocabulary effectively, which is also in line with the response to the questionnaire regarding the external and internal factors. The external factor is the application of learning methods with less encouragement, and internal factors are related to students' learning motivation to be more active in mastering Japanese vocabulary.